La planificación financiera y su impacto en la rentabilidad de la empresa DICEL en tiempos de pandemia COVID-19. - Ilvis Tapia, Karla Fabiana (2022)
The present research work aims to determine what was the impact of financial planning on the profitability of the company DICEL of the city of Riobamba in times of pandemic COVID-19. Considering the implications involved in the situation, the research is developed in a scenario where the low levels of productivity due to the growing demand for electricity services and internet connections. This is why this research includes the use of the hypothetical-deductive method in correlation with the explanatory method. Framed under the descriptive, correlational and mixed research approach based on the non-experimental design. For the study basis, the financial information was selected, reviewed, and evaluated through the analysis of the financial statements. For data collection, various techniques and instruments were used, specifically the interview and direct observation, which allowed the process of analyzing the information to be organized, relevant and clear. The study area reflects that the company has problems in terms of weak financial planning, i.e., activities are not developed technically but in a routine manner, causing deficiencies in inventory management, high production costs, increase in accounts receivable, which causes poor management and control of financial resources. Therefore, a financial planning model is proposed with strategies that contribute to maximizing the profitability of the company through good financial administration, control, and correct decision-making on income, costs, expenses, and projections to increase the efficiency and effectiveness in the fulfillment of the objectives set by the company.